CYBER SECURITY MANAGEMENT AND STRATEGIC INTELLIGENCE - Trim, Peter R. J.; Lee, Yang-Im (ROUTLEDGE, 2025)
"Within the organization, the cyber security manager fulfils an important and policy-oriented role. Working alongside the risk manager, the Information Technology (IT) manager, the security manager and others, the cyber security manager's role is to ensure that intelligence and security manifest in a robust cyber security awareness programme and set of security initiatives that when implemented help strengthen the organization's defences and those also of its supply chain partners. Cyber Security Management and Strategic Intelligence emphasises the ways in which intelligence work can be enhanced and utilized, guiding the reader on how to deal with a range of cyber threats and strategic issues. Throughout the book, the role of the cyber security manager is central, and the work undertaken is placed in context with that undertaken by other important staff, all of whom deal with aspects of risk and need to coordinate the organization's defences thus ensuring that a collectivist approach to cyber security management materializes. Real-world examples and cases highlight the nature and form that cyber-attacks may take and reference to the growing complexity of the situation is made clear. In addition, various initiatives are outlined that can be developed further to make the organization less vulnerable to attack. Drawing on theory and practice, the authors outline pro-active, and collectivist approaches to counteracting cyber-attacks that will enable organizations to put in place more resilient cyber security management systems, frameworks and planning processes. Cyber Security Management and Strategic Intelligence references the policies, systems and procedures that will enable advanced undergraduate and postgraduate students, researchers, and reflective practitioners to understand the complexity associated with cyber security management and apply a strategic intelligence perspective. It will help the cyber security manager to promote cyber security awareness to a number of stakeholders and turn cyber security management initiatives into actionable policy of a proactive nature"-- Provided by publisher.
Keywords: Business enterprises -- Computer networks -- Security measures.; Computer security.; Computer crimes -- Prevention.; Corporations -- Security measures.; elektronické knihy; electronic books